Light Amplification and Efficient Electroluminescence from a Solution‐Processable Diketopyrrolopyrrole Derivative via Triplet‐to‐Singlet Upconversion. (9th February 2021) - Shukla, Atul; McGregor, Sarah K. M.; Wawrzinek, Robert; Saggar, Siddhartha; Moore, Evan G.; Lo, Shih‐Chun; Namdas, Ebinazar B.
Abstract: Over the years, achieving efficient electroluminescence (EL) while simultaneously having low light amplification thresholds under optical excitation has been the key to progression toward the long‐thought objective of electrically pumped organic lasers. While significant progress in this regard has been made for organic semiconductors emitting in the blue–green region of the visible spectrum, organic laser dyes with low‐energy emission (>600 nm) still suffer from high amplified spontaneous emission (ASE) thresholds and low external quantum efficiencies (EQEs) in devices. Herein, low ASE thresholds and efficient EL are reported from a solution‐processable organic laser dye dithiophenyl diketopyrrolopyrrole (DT‐DPP). The ASE threshold of 4 µJ cm −2 at the wavelength of 620 nm is obtained while making constructive use of triplet excitons by doping DT‐DPP in a green‐emitting host matrix, which exhibits thermally activated delayed fluorescence (TADF). The organic light‐emitting diode fabricated from this system gives a high EQE of 7.9% due to the efficient utilization of triplet excitons. Transient EL studies further show that a high reverse intersystem crossing rate is crucial in achieving lasing under electrical pumping from such TADF‐assisted fluorescent systems. Abstract : Thermally activated delayed fluorescence (TADF)‐assisted fluorescence is successfully utilized to boost light‐amplification properties and device efficiencies for a diketopyrrolopyrrole derivative. An extremely low amplified spontaneous emission (ASE) threshold (4 µJ cm −2 ) is achieved along with high device external quantum efficiencies (8%). The triplet exciton confinement on the TADF is demonstrated to reduce singlet‐triplet annihilation losses while allowing the generated triplet excitons to be harvested.